Towards a Biopsychosocial Psychiatry. Issue 2 (3rd April 2019) - Strauss, John; Bernard, Pauline; Harper, Annie
Abstract : Objective: Constructing a meaningful biopsychosocial model for the mental health field has been extremely elusive. Identifying the linkages between the biological, psychological and social domains has been especially daunting. There has been important progress in clarifying general correlations of certain social factors related to the mental health of individuals and in developing training programs to recognize these social factors. However, efforts have usually focused on broad correlations and there have been serious deficiencies in developing methods for understanding and dealing with the specific processes happening at the psychological and social interface. For this reason, it would be important to be able to do such things as for example have a means to clarify the processes that connect the individual's mental health and its specific interactions with his or her social class. In this report we suggest two approaches that can contribute to solving this problem. Methods: We will describe approaches from the fields of anthropology and microhistory that link the specific experiences of the individual and the nature of the social context in which he or she finds him/herself. Results: Careful application of certain anthropological and history study methods that "take seriously" the specific interactions between the environmental situation and the individual can provide approaches to improved understanding of the relevant variables and the causal links between "psycho" and "social" in the biopsychosocial model. Conclusions: Teaching and applying these principles in treatment and research can contribute to a more effective model of biopsychosocial interactions in the mental health field.